JDBC Recipes: A Problem-Solution Approach - Parsian, Mahmoud (Apress, 2012)
This book provides complete and working solutions for performing database tasks using JDBC. You can cut and paste solutions from this book to build your own JDBC database applications. All the solutions have been compiled and tested against two leading databases: MySQL and Oracle. This book is ideal for anyone who knows some Java (can read/write basic Java programs) and a little JDBC (can read/write basic queries using JDBC and SQL) and wants to learn more about JDBC. Each section of this book is a complete recipe (including the database setup, the solution, and the MySQL and Oracle solutions), so you can use the code directly in your projects (although sometimes you may need to cut and paste the sections you need).5